Anti-copy of 2D Barcode Using Multi-encryption Technique - Phumpho, Suwilai; Payakkawan, Poomyos; Jansri, Anurak; Tongaram, Direk; Promprayoon, Chirasak; Keattipun, Pithuk; Ruengpongsrisuck, Boonchu; Punnua, Chanachai; Areejit, Satree; Sooraksa, Pitikhate (My University, 2014)
2D barcode can be found largely at product of department store. The general purpose of 2D barcode is to identify product. Process of 2D barcode is run in the assembly production line. Nowadays, the simple 2D barcode can be easily copied. Then, this paper proposes new technique to generate 2D barcode. The technique is multi encryption by chaotic equation that is very difficult to reproduce. In experimental design, 2D barcode can be used only one-time and can be recorded into decoding system to protect repeating. This paper has led to real benefit for Fresh Group company limited in Thailand.
Keywords: 2D barcode; Anti-copy; Chaos; Encryption; Security